(untitled) (Research, Society and Development, 2022)
This article aims to: Analyze the process of creation of the Marine Extractive Reserve of Canavieiras, South Marine-Coastal Protected Area, in the State of Bahia, Brazil, highlighting the interests that permeated its creation and implementation process, community and associative organization; to highlight the importance of this Resex for environmental conservation, based on the mosaic structure of its landscape, in two different moments, the years 2000 and 2018 - before and after its creation. As a methodological approach, bibliographic and documentary surveys were carried out, in loco visits in the beneficiary communities with the implementation of the Resex and information collection, as well as the elaboration of maps of land use and occupation, through the ArcGis software. The research results showed that there were several conflicts of interest in the process of creation and implementation of this Resex, especially in the municipality of Canavieiras, due to enterprises that felt harmed with its implementation. Comparing the landscape mosaic of this Resex, it was possible to infer that the vegetation cover is in good conservation conditions in its area of ​​coverage, especially with regard to the mangrove ecosystem when compared to other areas occupied with forest formations in the interior of the territory of the municipalities of Canavieiras and Belmonte. Since these were being suppressed by pastures or agriculture and pasture association. In addition, in loco it was identified the occurrence of certain effects within the Resex from projects not belonging to extractivists, such as the drainage next to the Campinhos community, harming the underground water resource used by it, something that cannot be captured by the maps.